Exploring therapists’ experiences of using Eye Movement Desensitisation and Reprocessing Therapy with children and young people - Shipley, Gemma (2024)
Eye Movement Desensitisation and Reprocessing (EMDR) therapy was developed by Francine Shapiro in 1989 as a psychotherapeutic intervention for adult clients diagnosed with Post-Traumatic Stress Disorder (PTSD). Over time, empirical support for the intervention’s efficacy and effectiveness has grown and EMDR has been recommended as an evidence-based treatment option in the United Kingdom by the National Institute for Health and Care Excellence (NICE, 2018). Furthermore, the clinical utility of EMDR with other client groups, such as children and young people, has been explored, with research and clinical studies offering promising results. However, when working with children and young people it is well established that treatment protocols originally developed with adult clients in mind, often require adaptation to ensure their developmental appropriateness. It has been suggested that therapists typically make adaptations to standardised protocols based on their areas of expertise, often drawing on and integrating other therapeutic modalities in the service of promoting meaningful engagement and enhancing outcomes for children and young people. However, what is not clear within the current literature is how therapists experience adapting and delivering EMDR to children and young people.